Al-Majāz fī al-Qur’ān al-Karīm (Dirāsah al-Muṣṭalahīyya wa al-Lughawīyya) - Sukamto Said (Al-Jami'ah Research Centre, 1997)
A debate on majāz (metaphor) in the Quran has begun a long time ago. The different opinions are actually caused by the different view point, e.q. the difference on majāz (metaphor), and the functions of language. In fact, each group tries to purify the Quran as the word of Allah from any lackness. Since they are different in this issue, they disagree on whether or not majāz exists in the Quran. majāz is sometime seen equal to a lie. This is because majāz does not hold literary meaning, or it is employed when the real expression (tarkib haqiqi) is impossible to be found. Impossibility is not for Allah, therefore those who see majāz equal to a lie reject the notion of majāz in the Quran. For those who consider majāz to be in the Quran do not see majāz as a lie due to its unreal meaning. The use of majāz does not necessarily indicate the lackness of Allah, but it shows rather the shortage of human language, that is the shortage of its descriptive function. Majāz style is used to express abstract meanings, such as beauty, dignity, mighty and so on. Using words for metaphorical meanings allows people to express their imagination in broad range by using the language symbols- This is one of language functions. Another aspect function of language is transformative function. This allows people to transform anything they read or hear concerning any aspects outside themselves into their mind in a form of symbols acquainted to them. The transformation is done by comparing the new knowledge with the old one already existed in their mind. Here, the metaphorical process occurs. Finally, it can be said that the use of majāz in the Quran is not merely language flower, or even a lie, but it is a need; a need of expression and understanding. The discussion around this problem is more complex because of the different views on the meaning of majāz and the functions of language. If this issue can be solved. the debate on majāz in the Quran can be reduced.